Examining the relationship between governance and gross fixed capital formation in Sub-Saharan Africa - Machobani, Dennis (University of the Witwatersrand, Johannesburg, 2024)
This study delves into the intricate relationship between governance and Gross Fixed Capital Formation (GFCF) in Sub-Saharan Africa (SSA), aiming to address the substantial infrastructure deficit in the region. Employing the System GMM methodology, the primary research question focuses on understanding the correlation between institutions and GFCF in SSA. Subsequent sub-questions delve into the relationships between political stability and GFCF, as well as the composite index of institutions and GFCF. Policy recommendations highlight the pivotal role of good governance, advocating for reforms, institution strengthening, and enhanced transparency. The study's outcomes emphasize the intricate interplay of diverse factors impacting GFCF, prompting policymakers to adopt comprehensive strategies for sustainable development. Persistent effects of past investment choices underscore the necessity for continuous efforts to incentivize investment. Key determinants such as trade policies, current account balances, gross domestic savings, and government expenditure are identified, suggesting targeted interventions to stimulate private sector engagement and cultivate an environment conducive to heightened investment in Sub-Saharan Africa.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Gross fixed capital formation; Sub-Saharan Africa; SDG-8: Decent work and economic growth; SDG-11: Sustainable cities and communities